Pengaruh Hidroterapi Terhadap Penurunan Tekanan Darah Pada Lansia di UPT Pelayanan Sosial Tresna Werdha Provinsi Riau - Chairil Chairil; Roma Della (LPPM UMRI, 2022)
Abstract One of the many health problems experienced by the elderly is the cardiovascular system, namely an increase in blood pressure. The 2013 Riskesdas report shows that the prevalence of hypertension in adults in Riau Province is 20.9%, in Pekanbaru City is 18.1%, and The prevalence of hypertension tends to increase with age. For this reason, this service aims to provide an alternative for hypertension sufferers by doing a foot soak using warm water, the method is carried out by measuring the blood pressure of patients next compared to after soaking in warm water with a total of 23 male-19 and female patients 4 results From research and implementation, it is stated that there is a hydrotherapy mechanism that can reduce blood pressure in people with hypertension. Soaking the feet with hot water can heat the whole body, increasing blood circulation to the top and suppressing circulation. Scientifically, warm water has a physiological impact on the body. in the blood vessels where warm water makes blood circulation smooth